Papillomatosis in a raccoon (Procyon lotor) - Sanz, Alexandra; Miller, Erica; Harley, Nikki; Coffee, Laura (Wildlife Rehabilitation Bulletin, 2022)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Papillomaviruses are species-specific double-stranded DNA viruses with at least 50 species of mammals. Although well-studied in humans, papillomaviruses in the raccoon (<em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Procyon lotor<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">) are not well characterized, and few cases have been published. Therefore, when the disease is encountered in a rehabilitation center, definitive diagnosis and treatment in the raccoon can be unclear. This case study outlines the characteristic gross and histologic lesions of an affected individual to facilitate identification and treatment of this disease in the future. In the case of this juvenile raccoon, ulcerated exophytic lesions on the bridge of its nose and right forelimb digit were seen grossly, with the presence of koilocytes and hyperkeratosis observed histologically. These findings are consistent with other documented cases of papillomavirus in raccoons and canines. Affected raccoons do not require extensive treatment, as raccoon papillomatosis is considered self-limiting.